2020
DOI: 10.1108/sajbs-06-2019-0101
|View full text |Cite
|
Sign up to set email alerts
|

M-coupon's sharing behaviour on social media: intrinsic vs extrinsic motivation

Abstract: PurposeThe focus of this study lies in understanding the extrinsic vs intrinsic motivators which drive the m-coupon sharing behaviour in social networking sites (SNSs). A consumer can make promotional tool (in our case m-coupons) viral if the cues trigger an apt motivation. This study fills the need gap by identifying which motivations must be focused to make a promotional tool viral by the consumer especially in an emerging economy like India.Design/methodology/approachWe designed conceptual framework based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 152 publications
0
4
0
Order By: Relevance
“…Adding further, this research investigates the significance of intrinsic motivational drivers such as self-expression and customer engagement on social media along the line of Algesheimer et al [ 87 ], and Chai et al [ 11 ], in a comprehensive model. Several studies in the past used intrinsic and extrinsic motivation concept to explore behaviour [ 86 ], knowledge sharing behaviour [ 88 ], e-WOM behaviour [ 11 , 32 , 33 ]. In order to unearth this phenomenon further, applying intrinsic-extrinsic motivation, social exchange theory and self-presentation theory [ 81 , 89 ] have been adopted.…”
Section: Literature Review and Theoretical Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding further, this research investigates the significance of intrinsic motivational drivers such as self-expression and customer engagement on social media along the line of Algesheimer et al [ 87 ], and Chai et al [ 11 ], in a comprehensive model. Several studies in the past used intrinsic and extrinsic motivation concept to explore behaviour [ 86 ], knowledge sharing behaviour [ 88 ], e-WOM behaviour [ 11 , 32 , 33 ]. In order to unearth this phenomenon further, applying intrinsic-extrinsic motivation, social exchange theory and self-presentation theory [ 81 , 89 ] have been adopted.…”
Section: Literature Review and Theoretical Supportmentioning
confidence: 99%
“…Apart from personality traits, intrinsic and extrinsic rewards (motivational drivers) also played a crucial role in writing reviews online [ 32 ], e-WOM intention [ 11 ], sharing behaviour on social media [ 33 ]. Considering motivational theory, Teichmann et al [ 34 ], found that extrinsic rewards such as self-presentation and opinion leadership had a strong effect on creating content online.…”
Section: Introductionmentioning
confidence: 99%
“…A vast amount of research on the impact of coupons and other such promotional tactics on consumers' purchase behavior has been conducted focusing on how such factors as price consciousness and coupon proneness influence redemption rates. In contrast, Sharma and Joshi (2021) investigate consumers' inclination to share M-coupons via social networking sites (SNSs), specifically in the South Asian context. The authors outline that motivation to share such digital coupons may be intrinsic and/or extrinsic, and they attempt to investigate how each of them impacts the willingness to share M-coupons via social sites, especially ones that are likely to be dominated by weak ties, infrequent indirect interactions and lack of emotional connection.…”
Section: Contributions Of Special Issue Articlesmentioning
confidence: 99%
“…We can expect that the rapidly decreasing online/offline dichotomy will eventually simply fade away (Appel et al, 2020). Sharma and Joshi (2021), the first article included in this special issue, reflects on the marketing implications of a relatively recent technological development: mobile coupons (M-coupons). M-coupons offer some obvious advantages for both marketers and consumers.…”
mentioning
confidence: 99%